Therapeutic aspects of Sydenham's Chorea: an update - Depietri, Greta; Carli, Niccolo; Sica, Attilio; Oliviero, Domenico; Costagliola, Giorgio; Striano, Pasquale; Bonuccelli, Alice; Frisone, Flavia; Peroni, Diego; Consolini, Rita; Foiadelli, Thomas; Orsini, Alessandro (Acta Biomedica Atenei Parmensis, 2022)
Sydenham’s Chorea (SC) is a hyperkinetic movement disorder associated with neuropsychiatric manifestations. It is believed to be caused by the autoimmune response following a group A beta-hemolytic streptococcal (GABHS) pharyngitis, and it is one of the major diagnostic criteria for Acute Rheumatic Fever (ARF) diagnosis.Despite having been known and studied for centuries, there are still no standardized therapies or official guidelines for SC treatment, so that it is necessarily left to physicians’ clinical experience. Antibiotic treatment, symptomatic therapies, and immunomodulatory treatment are the three pillars upon which SC patients’ management is currently based, but they still lack a solid scientific basis.The aim of this writing is precisely to review the state of the art of SC’s treatment, with an overview of the advances made in the last 5 years. However, since the therapeutic uncertainties are a mere reflection of the severe gap of knowledge that concerns SC’s pathogenesis and manifestations, the importance of high-quality research studies based on homogenized methodologies, instruments, and measured outcomes will also be stressed.